Ortografi Mushaf Al-Qur'an Nusantara Abad Ke-18 M: Kajian Manuskrip Mushaf al-Qur’an Batokan Kediri - Zaenatul Hakamah (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2022)
Abstract: This article examines the Qur’anic manuscript found in Batokan, Kediri. The manuscript, which was inherited from Mbah Abdurrahman Batokan, has been perceived by the residents to have a mystical history since its appearance, and to have connection with the charismatic figure of Diponegoro. One of the uniqueness of the manuscripts is that there is no waqf (stop) sign except for the third juz. This article studies the manuscript in two aspects, namely the orthography of the 18th century AD Archipelago manuscripts of the Qur’an; and the distinction of the Batokan Kediri Qur’anic manuscript and its relation to the socio-historical community. This paper concludes that the writing of the 18th century Archipelago manuscripts of the Qur’an, such as the Batokan manuscripts, was a manifestation of the influence of Islamic studies with regards to the struggle for independence and the formation of local culture. Furthermore, the Batokan Mushaf reflects a form of Islamic sacredness which functions as a talisman for the community.   Abstrak: Artikel ini mengkaji manuskrip mushaf al-Qur’an yang terletak di Batokan, Kediri. Manuskrip yang merupakan warisan Mbah Abdurrahman Batokan tersebut dianggap memiliki sejarah mistis atas kemunculannya, dan warga meyakini keterkaitan antara mushaf tersebut dengan sosok Pangeran Diponegoro. Keunikan pada manuskrip mushaf tersebut, salah satunya, adalah tidak adanya tanda waqf pada ayat-ayatnya kecuali hanya pada juz ketiga. Artikel ini mengkaji manuskrip tersebut dalam dua aspek, yaitu tentang ortografi mushaf al-Qur’an Nusantara abad ke-18 M; dan tentang distingsi mushaf al-Qur’an Batokan Kediri serta keterkaitannya dengan sosio-historis masyarakat setempat. Tulisan ini menyimpulkan bahwa penulisan mushaf al-Qur’an Nusantara abad ke-18 M, seperti mushaf Batokan, merupakan wujud dari pengaruh kajian keislaman terhadap upaya kemerdekaan dan terbentuknya budaya setempat. Selanjutnya, mushaf Batokan merefleksikan bentuk ekstraksi dari nilai sakralitas keislaman yang difungsikan sebagai “aji-aji” bagi masyarakat untuk dijadikan senjata batin para penduduknya.